Novel graphitic carbon nitride/graphite carbon/palladium nanocomposite as a high-performance electrocatalyst for the ethanol oxidation reaction. (10th February 2016) - Li, Zesheng; Lin, Runsheng; Liu, Zhisen; Li, Dehao; Wang, Hongqiang; Li, Qingyu
Graphical abstract: Novel graphitic carbon nitride/graphite carbon/palladium (Pd@g-C3N4/GC) electrocatalyst with excellent electrocatalytic performance and good electrochemical stability are developed for the ethanol oxidation reaction in alkaline medium. Highlights: Graphite carbon support was massively prepared by a cost-effective catalytic strategy. Ultra-thin g-C3 N4 was successfully deposited on the surface of graphite carbon support. Three-phase boundary from graphite carbon, g-C3 N4 and Pd was successfully formed. Nitrogen-rich g-C3 N4 effectively promoted the electrochemical activity of Pd metal. Abstract: Graphitic carbon nitride (g-C3 N4 ) possesses high nitrogen content with excellent chemical and thermal stability, which also shows inherent electrochemical properties. Due to the extremely low electronic conductivity, pure g-C3 N4 is usually restricted to electrocatalytic applications. In this study, we report the synthesis of graphite carbon (GC) supported g-C3 N4 and palladium (Pd) electrocatalyst with excellent electronic conductivity for the ethanol oxidation reaction. In virtue of the ultra-thin structure of g-C3 N4 deposited on the surface of GC, the crucial three-phase boundary from GC, g-C3 N4 and Pd component are successfully formed in Pd@g-C3 N4 /GC electrocatalyst. The electrocatalytic performances on ethanol electrooxidation of Pd@g-C3 N4 /GC, Pd@g-C3 N4, Pd@GC and Pd@amorphous carbon (AC) have been systematically investigated by the techniques of cyclic voltammetry and electrochemical impedance spectroscopy. The Pd@g-C3 N4 /GC displays the best electrocatalytic performances with a high oxidation peak current density of 2156 A/g Pd and low on-set potential of 0.32 V for the ethanol oxidation. The peak current density of Pd@g-C3 N4 /GC maintains at 1904 A/g Pd after 200 continuous cyclic voltammetry cycles. The Pd@g-C3 N4 /GC composite material might be one of candidate electrocatalysts for the ethanol oxidation reaction in direct ethanol fuel cells.